Resolution of severe oncogenic hypophosphatemic osteomalacia after resection of a deeply located soft-tissue tumour - Radaideh, A.R.M. (Multimed Inc., 2009)
Oncogenic osteomalacia is a rare metabolic bone disease characterized by phosphate leakage from the kidney and subsequent hypophosphatemia. It is caused by a phosphaturic factor produced by certain tumours. Removal of such tumours can completely cure the condition. Here, we report the case of a patient who was crippled with oncogenic osteomalacia. Extensive study revealed a tumour deeply located in the pelvis; removal of the tumour resulted in complete recovery. The tumour was identified as a mesenchymal tumour (mixed connective-tissue variant). The diagnostic evaluation, differential diagnosis, and treatment are discussed.